The Oxford handbook of Asian business systems - Witt, Michael A.; Redding, S. G. (Oxford : Oxford University Press, 2014)
"The Oxford Handbook of Asian Business Systems aims to address this imbalance by exploring the shape and consequences of institutional variations across the political economies of different societies within Asia. Drawing on the deep knowledge of 31 leading experts, this book presents an empirical, comparative institutional analysis of 13 major Asian business systems between India and Japan. To aid comparison, each country chapter follows the same consistent outline. Complementing the country chapters are eleven contributions examining major themes across the region in comparative perspective and linking the empirical picture to existing theory on these themes. A further three chapters provide perspectives on the influence of history and institutional change. The concluding chapters spell out the implications of all these chapters for scholars in the field and for business practitioners in Asia."--Publisher's website.
1. Introduction -- 2. China: authoritarian capitalism -- 3. Hong Kong: hybrid capitalism as catalyst -- 4. India: from failed developmental state towards hybrid market capitalism -- 5. Indonesia: oligarchic capitalism -- 6. Japan: coordinated capitalism between institutional change and structural inertia -- 7. Laos: frontier capitalism -- 8. Malaysia: personal capitalism -- 9. The Philippines: inequality-trapped capitalism -- 10. Singapore: open state-led capitalism -- 11. South Korea: plutocratic state-led capitalism reconfiguring -- 12. Taiwan: SME-oriented capitalism in transition -- 13. Thailand: post-developmentalist capitalism -- 14. Vietnam: post-state capitalism -- 15. Business groups in Asia: an institutional perspective -- 16. Corporate governance and business systems in Asia -- 17. Culture and the business systems of Asia -- 18. Employment relations and human resource Management in Asia: explaining patterns in asian societies -- 19. Financial systems in Asia: where politics meets development -- 20. MNEs in Asian business systems -- 21. National R&D systems and technology development in Asia -- 22. The Co-evolution of global sourcing of business support functions and the economic development of Asian emerging economies -- 23. Social capital in Asia: its dual nature and function -- 24. The role of the state in Asian business systems -- 25. A survey of strategic behaviour and firm performance in Asia -- 26. Pictures of the past: historical influences in contemporary Asian business systems -- 27. Beyond production: changing dynamics of Asian business groups -- 28. Change and continuity in East Asian business systems -- 29. Asian susiness systems: implications and perspectives for comparative business systems and varieties of capitalism research -- 30. Asian business systems: implications for managerial practice.
Series statement from dust jacket.
Includes bibliographical references and index.
Keywords: Industrial management -- Asia; Comparative management; Business enterprises -- Asia; Business enterprises; Comparative management; Industrial management; Asia